Ray tracing by simulated annealing: Bending method - Bona, Andrej; Slawinski, M.; Smith, P. (Society of Exploration Geophysics, 2009)
We propose a new ray-tracing method based on the concept of simulated annealing. Using this method, we find rays between fixed sources and receivers that render traveltime globally minimal. With our method, we are able to construct rays and their associated traveltimes to satisfactory precision in complex media. Furthermore, our algorithm can be modified to calculate rays of locally minimum traveltime, such as reflected rays, by constraining the ray to pass through a set of points that we are free to specify.